Pengaruh Jus Buah Nanas Kombinasi Madu sebagai Penurun Tekanan Darah pada Pasien Hipertensi - Lia Angelika; Nurul Annisa; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Hypertension is a disease characterized by an increase in blood pressure in systolic and diastolic blood vessels that exceeds the normal blood pressure on repeated examinations. Pineapple and honey empirically and scientifically can be efficacious for lowering blood pressure. The purpose of this study was to look at the characteristics of age, gender, smoking habits, exercise habits as well as the history of hypertension patient's disease and the effect and effectiveness of the administration of pineapple honey juice to reduce blood pressure in patients with hypertension at UPTD Tresanti Werdha Nirwana Puri Samarinda and on Jl. S.Parman 1 RT. 02 & RT. 03 Kelurahan Gunung Kelua Samarinda. The research design used was the Pretest and Posttest One Design Group, to as many as 9 patients. The study was conducted for 7 days, then every day patients were given treatment in the form of giving pineapple juice as much as 200 grams and 20 mL honey once a day and blood pressure was measured before and after treatment. The results of this study indicate a decrease in blood pressure in hypertensive patients who consume honey combination pineapple fruit juice.